2022
DOI: 10.3389/fphar.2022.887890
|View full text |Cite
|
Sign up to set email alerts
|

Zhi-Zi-Chi Decoction Reverses Depressive Behaviors in CUMS Rats by Reducing Oxidative Stress Injury Via Regulating GSH/GSSG Pathway

Abstract: Depression is one of the main diseases that lead to disability and loss of ability to work. As a traditional Chinese medicine, Zhi-zi-chi decoction is utilized to regulate and improve depression. However, the research on the antidepressant mechanism and efficacy material basis of Zhi-zi-chi decoction has not been reported yet. Our previous research has found that Zhi-Zi-chi decoction can reduce glutamate-induced oxidative stress damage to PC 12 cells, which can exert a neuroprotective effect, and the antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The CRS has been used in the current research as a model of generating depressive-like symptoms because it induces behavioral, neurological, and hormonal changes that are similar in some extent to how humans can experience depression. [33][34][35] The current experiment showed that CRS increased depressive-like behavior as evidenced by reduced sucrose grooming time in the splash test and swimming time in the FST as well as increased immobility time in the TST. Consistent with our results, in previous studies, CRS led to decreased sucrose consumption and grooming frequency in splash tests, and extended immobility time in the FST 36 and TST.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The CRS has been used in the current research as a model of generating depressive-like symptoms because it induces behavioral, neurological, and hormonal changes that are similar in some extent to how humans can experience depression. [33][34][35] The current experiment showed that CRS increased depressive-like behavior as evidenced by reduced sucrose grooming time in the splash test and swimming time in the FST as well as increased immobility time in the TST. Consistent with our results, in previous studies, CRS led to decreased sucrose consumption and grooming frequency in splash tests, and extended immobility time in the FST 36 and TST.…”
Section: Discussionmentioning
confidence: 48%
“…The CRS has been used in the current research as a model of generating depressive-like symptoms because it induces behavioral, neurological, and hormonal changes that are similar in some extent to how humans can experience depression. 33–35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geniposides is another important constituent in gardenia, and its medicinal value in gardenia fruit also has nonnegligible role. The abundant presence of flavonoids and geniposides is thought to account for the advantageous properties associated with gardenia fruits [ 31 ]. Therefore, analyzing the metabolites of gardenia fruits at different developmental stages is not only beneficial to understand the coloring process of gardenia fruits, but also beneficial to the development of gardenia fruits health products.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Modern research has shown that the anti‐depression effect of ZZCD might be associated with PKA/CREB/BDNF/TrkB/PSD‐95 pathway influenced by metabolic changes. 14 In addition, another study also indicated that ZZCD exerts potential antidepressant effects by reversing the imbalance of glutathione and oxidative stress 15 and increasing short‐chain fatty acid production and anti‐inflammatory bacteria, as well as reducing inflammatory and tryptophan‐metabolizing bacteria. 16 GF is a Chinese medicinal with a variety of pharmacological functions, such as anti‐inflammatory and antidepressant effect, as well as improving cognition and ischemic brain damage.…”
Section: Introductionmentioning
confidence: 99%